Implementasi Algoritme Speck pada Sistem Monitoring Detak Jantung dan Suhu - Mohamad Muhlason Nur Aziz; Rizal Maulana; Mochammad Hannats Hanafi Ichsan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
In every hospital, it is still relatively weak to safeguard the patient's personal data. Therefore, patient data in every hospital whose privacy data will be secured with the use of the speck algorithm. Securing patient data by applying a 32-bit and 64-bit speck algorithm, after that the encrypted Arduino A data is sent to Arduino B and then decrypted. In the patient data there are two measurements namely the heart rate data using the pulse sensor and body temperature data using the DHT11 sensor. The accuracy of the pulse sensor was 1.628% and the DHT11 sensor obtained 2.6%. Through the acquisition of these two sensors can formulate that the two sensors are very good. Testing the NRF24L01 module has a maximum distance of 35 meters if it exceeds that distance communication between NRF24L01 will be broken. Testing the results of the speck algorithm is implemented effectively into the Arduino Uno microcontroller. In general, the period of computing the system when the process of taking sensor data includes the decryption process in the form of 132.2 ms in 10 times the test.